(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to explore students’ perceptions towards the use of Aaron’s English YouTube Channel as a medium for learning English, especially in the areas of vocabulary, pronunciation, and grammar. The study was conducted on 15 students of TKR major at SMK PN 2 Purworejo using a qualitative method. Data were collected through open-ended questionnaires and analyzed thematically to capture the students’ insights. The findings show that most students perceive English as a difficult subject, especially due to challenges in pronunciation and grammar. However, YouTube, specifically Aaron’s English Channel, is seen as an effective supplemental tool for overcoming these difficulties. Students found the channel helpful because of its clear explanations, simple vocabulary, slow and accurate pronunciation, and English and Indonesian subtitles. Animations and relatable examples further increased engagement and comprehension. Most students reported improvements in pronunciation and vocabulary acquisition, and found the grammar lessons on the channel easy to follow. Although a few students experienced minimal progress, the overall perception remains positive. The study concludes that Aaron’s English Channel is a valuable learning resource, although improvements in interactivity and personalization could increase its impact. Most students would recommend the Channel to other English learners.